The effect of error remedial teaching common in mathematics in achievement Science subject for third year students At the Teachers Training Institute (Journal of the College of Basic Education, 2023)
There is no doubt that the development of science in general depends on mathematics and beAccompanying its development, as a result of the increasing reliance of science on mathematical methodsDetecting mathematical errors that affect students' achievement in science and addressing themImportance of student success and progress in science.The current research aims to find out the effect of remedial teaching for common errors in mathematicsIn the achievement of science, and in order to achieve this, the researcher put the following statistical hypothesis:There are no statistically significant differences in the average achievement of female students in the science houseThe experimental and control groups.The research sample consisted of (50) female students representing two divisions of the third grade at the Institute for PreparationParameters / Mansour.The researcher rewarded the students of the two groups in the variable of their achievement in mathematics for the yearPast, chronological age, monthly income, and parental education level.The researcher taught the two groups by herself over an entire semesterThe remedial method for common errors in mathematics when teaching the experimental groupShe used it when teaching the control group, and the researcher took science degrees at the end of the period